2009
DOI: 10.1038/ki.2009.1
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells decrease renal fibrosis in unilateral ureteral obstruction

Abstract: Mast cells regulate both inflammatory responses and tissue repair in human diseases but there are conflicting reports on the role of these cells in the pathogenesis of various kidney diseases. Here we measured mast cell function in unilateral ureteral obstruction, a well-characterized model of renal fibrosis, using Kit(W)/Kit(W-v) mice genetically deficient in mast cells, wild-type mice, and deficient mice reconstituted by adoptive transfer with mast cells from the wild-type animals. Mast cell-deficient mice h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
2
27
0
1
Order By: Relevance
“…Most studies have suggested that a reduction of mast cells, or their typical enzyme chymase, increases fibrosis (52)(53)(54)(55)(56), whereas others suggest the opposite (57,58). Thus, the potential therapeutic value of mast cell manipulation in fibrosis is uncertain (23,59).…”
Section: The Role Of Immune Cellsmentioning
confidence: 99%
“…Most studies have suggested that a reduction of mast cells, or their typical enzyme chymase, increases fibrosis (52)(53)(54)(55)(56), whereas others suggest the opposite (57,58). Thus, the potential therapeutic value of mast cell manipulation in fibrosis is uncertain (23,59).…”
Section: The Role Of Immune Cellsmentioning
confidence: 99%
“…The model of unilateral ureteral obstruction (UUO) generates progressive renal fibrosis that is independent of hypertension or systemic immune disease (8,26). The obstructed kidney after UUO results in marked renal hemodynamic and metabolic changes.…”
mentioning
confidence: 99%
“…Western blot analysis was performed as previousy described (21). In brief, protein samples were heated at 100˚C for 5 min and subjected to electrophoresis on 10 or 15% SDS gels.…”
Section: Introductionmentioning
confidence: 99%